2005
DOI: 10.4049/jimmunol.175.3.1706
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Peptide Involvement in T Cell Allorecognition Using Recombinant HLA Class I Multimers

Abstract: Alloreactive T cells are involved in injurious graft rejection and graft-vs-host disease. However, they can also evoke beneficial responses to tumor Ags restricted by foreign MHC molecules. Manipulation of these alloreactivities requires information on the basis of T cell allorecognition. The vigorous T cell response to foreign MHC molecules may arise from peptide-independent recognition of polymorphic residues of foreign MHC molecules or peptide-specific recognition of novel peptides presented by foreign MHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…Up to 10% of T cells of an individual can recognize foreign MHC class I and class II molecules (3,4), the magnitude of the alloreactive response being due to the large number of T cells stimulated by the hugely diverse array of self peptides on the nonself MHC molecules. Although alloreactive T cells can recognize structural determinants of the foreign MHC molecules independent of the bound peptides (5)(6)(7), it has become clear that, for most alloreactive T cells, recognition depends on peptides within the allo-MHC groove (5,6,8,9). Structural studies on alloreactive TCR complexed with allogeneic MHC molecules have confirmed the role played by peptides in alloreactivity (10,11).…”
mentioning
confidence: 87%
“…Up to 10% of T cells of an individual can recognize foreign MHC class I and class II molecules (3,4), the magnitude of the alloreactive response being due to the large number of T cells stimulated by the hugely diverse array of self peptides on the nonself MHC molecules. Although alloreactive T cells can recognize structural determinants of the foreign MHC molecules independent of the bound peptides (5)(6)(7), it has become clear that, for most alloreactive T cells, recognition depends on peptides within the allo-MHC groove (5,6,8,9). Structural studies on alloreactive TCR complexed with allogeneic MHC molecules have confirmed the role played by peptides in alloreactivity (10,11).…”
mentioning
confidence: 87%
“…Direct T-cell allo-recognition is the principal player in the initial vigorous immune response to allogeneic cells that causes acute rejection [21]. The direct recognition structure for T cells in allogeneic responses has been actively investigated [22][23][24][25][26]. Current belief in the field is that allogeneic T-cell responses, like syngeneic T-cell responses, are largely peptide specific, and that TCRs interact with allogeneic MHC in a manner that is almost indistinguishable from conventional recognition of antigenic peptide presented by self-MHC.…”
Section: Discussionmentioning
confidence: 99%
“…1,2527 While much remains to investigate, there is compelling evidence for the role of both the foreign MHC molecule and the peptide presented, though the relative contribution of each for different clones may not be equivalent. 20,2830 Although humans certainly did not evolve to mount an immune response in the context of organ transplantation, the germline T cell repertoire has been shown to be strongly enriched for MHC recognition. 31 Because the processes of positive and negative selection in the thymus take place after TCR α and β chain rearrangements have occurred, T cells developing in the thymus have the potential to recognize a diversity of potential HLA types; given the inherent cross-reactivity/degeneracy of TCR recognition due to the rotational flexibility of the TCR/MHC-peptide interface, 3235 alloreactivity can be thought of as the consequence of selection for weak recognition of self MHC-peptide complexes in the thymus in combination with selection against strong recognition of those same specificities 3639 Some clones exiting the thymus as naïve T cells may in fact be more strongly reactive to allogeneic HLA alleles, but have sufficient cross-reactivity to self-HLA/peptide complexes to survive positive selection.…”
Section: On the Origin And Diversity Of Alloreactive T Cellsmentioning
confidence: 99%